2017
DOI: 10.1103/physrevd.95.064040
|View full text |Cite
|
Sign up to set email alerts
|

Maximum magnetic moment to angular momentum conjecture

Abstract: Conjectures play a central role in theoretical physics, especially those that assert an upper bound to some dimensionless ratio of physical quantities. In this paper we introduce a new such conjecture bounding the ratio of the magnetic moment to angular momentum in nature. We also discuss the current status of some old bounds on dimensionless and dimensional quantities in arbitrary spatial dimension. Our new conjecture is that the dimensionless Schuster-WilsonBlackett number, cµ/JG 1 2 , where µ is the magneti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 75 publications
1
32
0
Order By: Relevance
“…The ratio |µ/J| is bounded above by 1/5, in agreement with the Barrow-Gibbons bound [48] |µ/J| ≤ 1, while the ratio |J|/M 2 satisfies the Kerr-like bound…”
Section: A Asymptoticssupporting
confidence: 80%
“…The ratio |µ/J| is bounded above by 1/5, in agreement with the Barrow-Gibbons bound [48] |µ/J| ≤ 1, while the ratio |J|/M 2 satisfies the Kerr-like bound…”
Section: A Asymptoticssupporting
confidence: 80%
“…Note that h µν is the induced metric on the field sheet and N µ ν is the projection tensor onto directions normal to the field sheet. The former equation (11) describes dynamics of field sheets acted on by a force associated with B, i.e., magnetic pressure; the latter equation (12) does conservation of the magnetic flux. This expression tells us that the dynamics of field sheets in FFE is similar to the dynamics of world sheets for Nambu-Goto strings.…”
Section: Field-sheet Formalism For Force-free Electromagnetic Fieldsmentioning
confidence: 99%
“…Comparing the above equation with Eqs. (11) and (12), we can easily notice that the only difference between the dynamics of field sheets and world sheets is the addition of the extra scalar quantity B, which describes the magnetic tension and pressure. (In the flat spacetime such a correspondence was discussed in Refs.…”
Section: Field-sheet Formalism For Force-free Electromagnetic Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oldest publications known to the authors are by Rauscher [5] and by Treder [6] and suggested the value c 4 /G as upper bound. More recent publications that focused specifically on the topic of the upper bound derived the value c 4 /4G, including those of Gibbons [2], Schiller [3], and Barrow and Gibbons [7,8]. Therefore we keep the factor 4 in the denominator.…”
Section: Introductionmentioning
confidence: 99%